Placental Adaptation: What Can We Learn from Birthweight:Placental Weight Ratio? - Hayward, Christina E.; Lean, Samantha; Sibley, Colin P.; Jones, Rebecca L.; Wareing, Mark; Greenwood, Susan L.; Dilworth, Mark R. (Frontiers in Physiology, 2016)
Appropriate fetal growth relies upon adequate placental nutrient transfer. Birthweight:placental weight ratio (BW:PW ratio) is often used as a proxy for placental efficiency, defined as the grams of fetus produced per gram placenta. An elevated BW:PW ratio in an appropriately grown fetus (small placenta) is assumed to be due to up-regulated placental nutrient transfer capacity i.e. a higher nutrient net flux per gram placenta. In fetal growth restriction (FGR), where a fetus fails to achieve its genetically pre-determined growth potential, placental weight and BW:PW ratio are often reduced which may indicate a placenta that fails to adapt its nutrient transfer capacity to compensate for its small size. This review considers the literature on BW:PW ratio in both large cohort studies of normal pregnancies and those studies offering insight into the relationship between BW:PW ratio and outcome measures including stillbirth, FGR and subsequent postnatal consequences. The core of this review is the question of whether BW:PW ratio is truly indicative of altered placental efficiency, and whether changes in BW:PW ratio reflect those placentas which adapt their nutrient transfer according to their size. We consider this question using data from mice and humans, focusing upon studies that have measured the activity of the well characterized placental system A amino acid transporter, both in uncomplicated pregnancies and in FGR. Evidence suggests that BW:PW ratio is reduced both in FGR and in pregnancies resulting in a small for gestational age (SGA, birthweight <10th centile) infant but this effect is more pronounced earlier in gestation (<28 weeks). In mice, there is a clear association between increased BW:PW ratio and increased placental system A activity. Additionally, there is good evidence in wild-type mice that small placentas upregulate placental nutrient transfer to prevent fetal undergrowth. In humans, this association between BW:PW ratio and placental system A activity is less clear and is worthy of further consideration, both in terms of system A and other placental nutrient transfer processes. This knowledge would help decide the value of measuring BW:PW ratio in terms of determining the risk of poor health outcomes, both in the neonatal period and long term.